A panel method based aerodynamic code for analysis of wind turbine blades - Lugones, Santiago Martín (2011)
The size of commercial wind turbines has increased dramatically in the last 25 years from approximately a rated power of 50kW and a rotor diameter of 10–15m up to today’s commercially available 5MW machines with a rotor diameter of more than 120 m. This development has forced the development of reliable numerical tools which enable the prediction of steady and unsteady aerodynamic loads not only in the wind turbine blades but also in the entire wind turbine construction, including tower, drive train, rotor and control system. Within this context, this paper presents a steady-state panel method formulation based code for aerodynamic load prediction in wind turbine blades. The formulation is fully three-dimensional accounting for wake and rotational angular speed effects. A 2MW wind turbine blade has been taken as a study case to demonstrate the code capabilities.